Penggunaan Kompos Blotong dan Pupuk Nitrogen pada Pembibitan Kakao (Theobroma cacao L.) - Astuti, Fitri; Parapasan, Yonathan; Hartono, Joko Sutopo Sugeng (Politeknik Negeri Lampung, 2015)
The purpose of this study was to determine the growth response of the cocoa seed to compost filter cake and nitrogen fertilizer application. This research has been carried out in State Polytechnic of Lampung teaching farm from September 2013 to March 2014 The method used was randomized block design (RBD) with factorial pattern consisting of two factors. The first factor is the compost filter cake, consisting of four levels, namely B0 = 0 g (control), B1 = 50 g, 100 g = B2, and B3 = 150 g per polybag. The second factor is the rate of nitrogen (Urea) fertilizer that consists of four levels, namely N0 = 0 g (control), N1 = 2.5 g, N2 =5.0 g and N3 = 7.5 g per polybag. The indicator used is cocoa seedlings (Theobroma cacao L.). Observations of plant height, leaf number, stem diameter, leaf width, root volume, shoot dry weight, root dry weight, and water content of the soil. Data were analyzed by analysis of variance with the level of accuracy of 5%, then if the calculated F value is greater than the F table, then followed by LSD test. The results showed the use of compost filter cake 150 g and 5.0 g of nitrogen fertilizer each per polybag give value stem diameter, root volume, stover dry weight, and root dry weight of cocoa seedlings higher than the other treatments.Keywords: filter cake compost, growing media, nitrogen fertilizer, Theobroma cacao L.Permalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/23